Implementation of the Azhari Curriculum in Islamic Religious Education at Darul Fikri Islamic High School: Implementasi Kurikulum Azhari Pada Pembelajaran Pendidikan Agama Islam di MA Darul Fikri - Ulya, Azizah Izzatul; Nurdyansyah (Indonesian Journal of Innovation Studies, 2026)
General Background Islamic religious education in modern secondary schools increasingly requires pedagogical innovation to move beyond passive lecture-based instruction. Specific Background Integrating international religious frameworks into national education standards presents distinct instructional opportunities for specialized madrasahs. Knowledge Gap However, empirical documentation regarding the combined application of the Al-Azhar curriculum and student-centered national frameworks remains limited. Aims This study analyzes the implementation, supporting factors, and operational challenges of integrating the Azhari curriculum with Kurikulum Merdeka at MA Darul Fikri. Results Qualitative field data reveal that combining classical Arabic texts with active learning strategies elevates student engagement, language acquisition, and practical community service outcomes. Novelty This research demonstrates an innovative hybrid model featuring intensive Arabic preparation, memorization methods, and field-based dakwah practice. Implications These findings provide strategic insights for Islamic educational institutions aiming to align traditional scholarship with modern academic requirements and global university entry standards. Key Findings Highlights Hybrid curriculum design successfully combines Egyptian classical Islamic texts with student-centered pedagogical practices. Intensive language orientation programs resolve initial Arabic proficiency barriers among secondary school learners. Field-based service initiatives translate theoretical religious concepts into practical community engagement skills. Keywords : Azhari Curriculum, Islamic Religious Education, Curriculum Integration, Academic Competence, Educational Innovation